Sufism and Personality Development (Khairulummah, 2021)
Personality development is the process of improvement in behaviors and attitudes to make an individual a unique person. Sufism brings about positive changes in the behaviors of individuals. The positive changes are brought through moral development within   inductive environment griped by building of character. Moral development guides through “Zuhud” and “Taqwa” for minimization of material luxuries, enhancement of repentance and self-purification. The purpose of moral development is achieved with an institution articulated with teacher-student (Murshid-Murid) relationships; this environment ensures the provision of guidance and scholarships for the engaged students. The engagement of students revolves around knowledge, awareness and behavior. In the dimension of knowledge students are helped with raising moral and spiritual awarenessto enhance firmness in faith and encouragement towards good deeds. In addition, behavioral (amal) dimension is covered with remembrance of Allah, optional prayers, fasting services, alms giving along with obligatory ones. All these behavioral deeds are performed with devotion for the sake of closeness “Taqarrub” to Allah. Finally, ma’rifat (Recognition) is applied to secure soundness in building of character.